Antihyperalgesic effect by herpes vector-mediated knockdown of NaV1.7 sodium channels after skin incision - Eisenried, Andreas; Klukinov, Michael; Yeomans, David C.; Tzabazis, Alexander Z. (NeuroReport, 2017)
Postincisional hyperalgesia and allodynia play an important role in perioperative medicine. NaV1.7 sodium channel has proven to be a key player in several pain states, including acute, inflammatory, and neuropathic pain. This study investigated the effects of silencing NaV1.7 through Herpes-based gene therapy with an antisense transcript on pain states after incision of the skin in rodents. Seventy-six Balb/C mice were subdivided into six groups and were treated with no virus, control virus, or NaV1.7 antisense vector before lateral hindpaw skin incision or sham procedure. All mice were tested for mechanical allodynia, cold allodynia, and thermal hyperalgesia. For time series analysis, a two-way analysis of variance with post-hoc Bonferroni testing was used. After incision mice developed significant hypersensitivity to mechanical, cold, and heat stimuli. The NaV1.7 antisense vector blocked the hypersensitivity to mechanical, cold, and heat stimuli that was normally observed 24 and 48 h after incision. We demonstrated that a gene therapy-based NaV1.7 knockdown affects postincisional hyperalgesia and allodynia. The data provide evidence that the incision model leads to periwound hypersensitivity after incision and that application of the NaV1.7 antisense virus prevents this sensitization. This then, in turn, provides presumptive support to the hypothesis that overexpression of the NaV1.7 channel is an important mechanism underlying hyperalgesia and allodynia following skin incision.
EVALuna2:36287